Spectrophotometric Determination Of Diacerin in Bulk and Pharmaceutical Formulation - NARENDRA KUMAR NYOLA; AND NARESH KALRA (International Journal of Pharma and Bio Sciences, 2010)
It is a disease modifying anti-rheumatoid drug used in the treatment of Osteoarthritis and chronic inflammatory arthritis. Various methods of analysis are available but are time consuming and expensive. A simple, rapid and accurate colorimetric method has been developed for the estimation of diacerein in bulk and pharmaceutical dosage forms, method are based on pink colored complex formation between diacerein with sodium hydroxide which shows maximum absorbance at 514nm .The linearity was found to be 10-50µg/ml. The developed method was found to be precise and accurate form the statistical validation of the analysis data.